Gender Related Stereotypes and their impact on Leadership - Raza, Amber (JISR management and social sciences & economics, 2010)
Gender stereotypes and transformational leadership can be viewed through the lens of implicit leadership theories (ILTs). Implicit theory suggests that one’s idea of what effective leadership is has a large impact on leadership ratings and as a result, leadership questionnaire often yield biased ratings of leadership behavior (Rush, Thomas and Lord, 1977). Maher (1997) has examined gender related stereotypes and concluded that men may have similar ILTs for male and female leaders but women may have different ILTs for both genders. Female leaders attribute their use of relational styles to their transformational leadership whereas men feel that their power and direct styles contribute to transformational leadership (Komives, 1991). This may suggest that women have ILTs of transformational leadership that include more developmental and nurturing behaviors than men. This paper will highlight the various traits associated with male and female leaders and its impact on the workplace. Most research journals tend to focus on quantitative approach. However, this paper explores the theory of transformational leadership through a case study approach. While these interviews and accounts may not be generalizable, however they could provide insights to the already conducted quantitative work.